Anticorrosion compositions based on polyurethane with fillers from carbon nanotubes, iron and aluminium oxides for protection of metal surfaces - Suslyaev, Valentin I.; Debelov, Vladislav A.; Vlasov, Yury A.; Debelova, Natalia N.; Dorozhkin, Kiril V.; Badiin, Alexander V. (Journal of the Belarusian State University. Physics, 2025)
Hydrophobic properties of composite materials based on polyurethane with fillers of carbon nanotubes, iron and aluminium oxides are considered. The data on the corrosion rate of St09G2S steel coated with a 0.5 mm thick layer of composites in aqueous solutions of sodium chloride, sulfate and carbonate salts are presented. It is shown that the most effective is the composition including a polymer with a filler from finely dispersed iron(III) oxide. The results of experimental studies of the dependence of electromagnetic response spectra, namely reflection, transmission and absorption coefficients of flat material samples are presented. The anticorrosion properties of the proposed composites were tested by comparing the electromagnetic response from dry and immersed in water samples using terahertz time-domain spectroscopy (THz-TDS) in the frequency range of 0.1–1.6 THz on a real-time spectrometer T-SPEC-1000 (Teravil, Lithuania). It was found that the values of dielectric permittivity and dissipation factor allow to determine the boundary conditions, in which polymer composites can be effectively used as anticorrosion coatings on metal surfaces.
Keywords: corrosion protection; composites; polyurethane; iron oxide; aluminium oxide; carbon nanotubes